2018
DOI: 10.1002/tox.22575
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tebuconazole on cytochrome P450 enzymes, oxidative stress, and endocrine disruption in male rats

Abstract: The major objective of the present study was to determine the ability of a triazole fungicide tebuconazole to induce cytochrome P450-dependent monooxygenases, oxidative stress, and endocrine-disrupting activity using male rats treated with tebuconazole at 10, 25, and 50 mg/kg p.o. once daily for 28 days. In liver, tebuconazole dose-dependently increased microsomal contents of cytochrome P450 and cytochrome b and the activities of NADPH-cytochrome P450 reductase, 7-ethoxyresorufin O-deethylase, methoxyresorufin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 46 publications
2
23
0
1
Order By: Relevance
“…Tebuconazole is a fungicide that has been frequently detected in agriculture systems at concentrations that affect endocrine function in organisms. For instance, it has been found to cause oxidative stress and endocrine disruption in rats (Yang et al 2018) and developmental toxicity associated to thyroid dysfunction in zebrafish (Li et al 2020). Finally, imazethapyr has also been reported by causing metabolic alterations in Cyprinus carpio (Moraes et al 2011), genotoxicity in tadpoles of Rhinella arenarum and Hypsiboas pulchellus species (Carvalho et al 2019;Perez-Iglesias et al 2017;Perez-Iglesias et al 2015), and also in mammalian cells (Soloneski et al 2017); however, the toxicity of herbicide is poorly characterized and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Tebuconazole is a fungicide that has been frequently detected in agriculture systems at concentrations that affect endocrine function in organisms. For instance, it has been found to cause oxidative stress and endocrine disruption in rats (Yang et al 2018) and developmental toxicity associated to thyroid dysfunction in zebrafish (Li et al 2020). Finally, imazethapyr has also been reported by causing metabolic alterations in Cyprinus carpio (Moraes et al 2011), genotoxicity in tadpoles of Rhinella arenarum and Hypsiboas pulchellus species (Carvalho et al 2019;Perez-Iglesias et al 2017;Perez-Iglesias et al 2015), and also in mammalian cells (Soloneski et al 2017); however, the toxicity of herbicide is poorly characterized and needs to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…TEB has been considered an endocrine‐disrupting chemical ,it could affect the reproduction and development of offspring in utero and increase the anogenital distance of female offspring (Taxvig et al, ). Previous studies demonstrated that TEB could produce anti‐androgenic effects in adult male rats with reduced serum testosterone level and sperm number (Yang et al, b). Common features of the azole fungicides epoxiconazole, prochloraz, and TEB were that they increased gestational length in dams, virilized female pups, and affected steroid hormone levels in fetuses and dams (Vinggaard, Nellemann, Dalgaard, Jørgensen, & Andersen, ; Vinggaard et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…To the best of our knowledge, the impact of FDO on CYP1A1 and CYP1A2 expression and EROD activity has not been shown before, but it was shown by Wetmore et al (2014) that FDO is mainly metabolized by CYP1A2. Effects of DIF, PPC and TBC on CYP1A1 and/or CYP1A2 expression or activity have been demonstrated previously (Egaas et al 1999;Knebel et al 2019b;Yang et al 2018;Zhang et al 2017). An increased metabolism of triazoles might be the underlying cause for enhanced steatotic effects, if not the parental triazole compounds, but their metabolites are the causative agents for steatosis.…”
Section: Discussionmentioning
confidence: 77%